Efficacy and safety of the oral Janus kinase inhibitor peficitinib (ASP015K) monotherapy in patients with moderate to severe rheumatoid arthritis in Japan: a 12-week, randomised, double-blind, placebo-controlled phase IIb study. Issue 6 (15th December 2015) - Takeuchi, Tsutomu; Tanaka, Yoshiya; Iwasaki, Manabu; Ishikura, Hiroaki; Saeki, Satoshi; Kaneko, Yuichiro
Abstract : Objective: To evaluate the efficacy, safety and dose response of a novel oral Janus kinase inhibitor, peficitinib (ASP015K), as monotherapy in Japanese patients with moderate to severe rheumatoid arthritis (RA). Methods: In a 12-week, double-blind study, 281 adult patients with RA with active disease not on concomitant disease-modifying antirheumatic drug therapy were randomised equally to once-daily placebo or peficitinib 25, 50, 100 and 150 mg. The primary endpoint was American College of Rheumatology (ACR) 20 response in the peficitinib treatment groups versus placebo at week 12. Results: Mean age was 53.0 years, 81.1% were female and 25.3% had previously used antitumour necrosis factor therapy. Peficitinib 50, 100 and 150 mg each showed statistically significantly higher ACR20 response rates compared with placebo, and response rates increased up to 150 mg with a statistically significant dose response. The total incidence of treatment-emergent adverse events (TEAEs) was similar between the placebo (64.3%) and peficitinib 25, 50, 100 and 150 mg groups (70.9%, 64.9%, 52.7% and 67.2%, respectively). TEAEs occurring more frequently in the peficitinib group compared with the placebo group included nasopharyngitis, increased blood creatine phosphokinase and diarrhoea. No cases of serious infections were reported. Herpes zoster occurred in four patients (two each in peficitinib 25 and 100 mg). Conclusions: Treatment with peficitinib as monotherapy for 12 weeks in Japanese patients with moderate to severe RA is efficacious and showed acceptable safety profile. These findings support further developments of peficitinib for RA treatment. Trial registration number: NCT01649999; Results.